Redefining the Architecture of Educational Leadership to Strengthen the Organizational Capabilities of Educational Institutions - Mohamad Hisyam Syafa'at; Nur Annisa Almaidah; Ainur Rofiq (Civiliza Publishing, Indonesia., 2026)
The increasingly rapid changes in the educational environment have shifted the leadership paradigm from merely performing administrative functions to the ability to build organizational capabilities that are adaptive, innovative, and sustainable. This study aims to reconstruct the educational leadership architecture in strengthening the organizational capabilities of Darussyafah Genteng Junior High School in Banyuwangi. This study employs a qualitative approach using a case study design to examine the reconstruction of the educational leadership architecture in strengthening organizational capabilities at Darussyafah Genteng Junior High School in Banyuwangi. Data were collected through observation, in-depth interviews, and documentation from four informants selected using purposive sampling. Data analysis followed the model proposed by Miles, Huberman, and Saldaña through data condensation, data presentation, and conclusion drawing, utilizing the processes of open coding, axial coding, and selective coding. Data validity was ensured through source triangulation, methodological triangulation, and member checking. The results of this study indicate that the reconstruction of educational leadership architecture strengthens organizational capabilities through three main dimensions: strategic vision-based leadership, the distribution of leadership through the empowerment of organizational actors, and organizational governance that integrates coordination and decision-making. These findings indicate that organizational capabilities are built through a leadership system that integrates vision, organizational structure, collaborative culture, and governance. This study contributes to expanding the study of educational leadership from the approaches of Strategic Leadership, Instructional Leadership, and Distributed Leadership toward the perspective of Leadership Architecture as a configuration of organizational systems that supports adaptive, collaborative, and sustainable organizations and serves as a reference for leadership development in educational institutions.